BIOECOLOGICAL POTENTIAL OF APIDEA IN CAUCASUS - M. A. Abakarova; A. R. Gasanov (Юг России: экология, развитие, 2014)
For the first time an analysis of bioecological potential bee in their areas of settlement in the territory of Dagestan is made. Designed a scientifically sound system of measures for the conservation and restoration of biological diversity of bees in the Republic of Dagestan.